2021
DOI: 10.1038/s41419-021-03874-7
|View full text |Cite
|
Sign up to set email alerts
|

G-MDSCs promote aging-related cardiac fibrosis by activating myofibroblasts and preventing senescence

Abstract: Aging is one of the most prominent risk factors for heart failure. Myeloid-derived suppressor cells (MDSCs) accumulate in aged tissue and have been confirmed to be associated with various aging-related diseases. However, the role of MDSCs in the aging heart remains unknown. Through RNA-seq and biochemical approaches, we found that granulocytic MDSCs (G-MDSCs) accumulated significantly in the aging heart compared with monocytic MDSCs (M-MDSCs). Therefore, we explored the effects of G-MDSCs on the aging heart. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…It has been shown that S100A8 could induce cellular senescence-like changes in bovine oviduct epithelial cells (Nakamura et al 2019). Similarly, S100A8/A9 promoted aging-related cardiac fibrosis in myeloid-derived suppressor cells (Sun et al 2021). At the organ level, in lungs, for example, aging per se was followed by CS and concomitant upregulation of S100A8 and increased severity of lung inflammation (Rashid et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that S100A8 could induce cellular senescence-like changes in bovine oviduct epithelial cells (Nakamura et al 2019). Similarly, S100A8/A9 promoted aging-related cardiac fibrosis in myeloid-derived suppressor cells (Sun et al 2021). At the organ level, in lungs, for example, aging per se was followed by CS and concomitant upregulation of S100A8 and increased severity of lung inflammation (Rashid et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin-EDA and TLR2/4 were matched in cardiac fibrosis, causing myofibroblasts to begin producing collagen I and III ( 30 ). Following the combination of S100A8/A9 and TLR4, which was intended to produce cardiac fibrosis, the expression of α-SMA, collagen 1A1, and 3A1 mRNA was also enhanced in fibroblasts ( 31 , 32 ).In pulmonary fibrosis, HSP90 and uric acid react with TLR2/4, aggravating the expression of TIMP-1 and the synthesis of fibronectin ( 33 ). S100A4 is also associated with TLR4 leading to elevated α-SMA expression and increased collagen I synthesis during pulmonary fibrosis ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“… 28 , 29 Furthermore, the profibrotic function of MDSCs have already been described in different organs and conditions. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…Even more interestingly, MDSCs may stimulate fibrosis either by secreting pro‐fibrotic mediators (IL6, TGF‐β, VEGF e PDGF), by differentiating in collagen‐producing fibrocytes, or by releasing proline (a major component of collagen and catabolite of Arginase‐1‐mediated reactions) 28,29 . Furthermore, the profibrotic function of MDSCs have already been described in different organs and conditions 30,31 …”
Section: Discussionmentioning
confidence: 99%